Oral administration of Garcinia dulcis flower extract lowers arterial blood pressure of 2-kidneys-1-clip renovascular hypertensive rat - Nattaya Thongsepee; Wilawan Mahabusarakam; Sophapun Ekarattanawong; Umarat Srisawat; Pongsakorn Martviset; Noppadon Suttirak; Siriphun Hiranyachattada (Penerbit Universiti Kebangsaan Malaysia, 2022)
The hexane insoluble fraction of the Garcinia dulcis (GD) flower extract comprises mainly camboginol and morelloflavone which possess potent in vivo and in vitro antioxidant properties. This study aimed to evaluate the effects of 4-week oral administration of GD flower extract on the arterial blood pressure (ABP) and the excretory function of the kidney in the 2-kidneys-1-clip (2K1C) renovascular hypertensive rats (total=12) compared to sham operated (SO) normotensive Wistar rats (total=12). Four weeks after hypertensive-induced surgery, either 50 mg/kg BW GD flower extract or vehicle was orally administered to the 2K1C or SO groups (n=6/group) daily for four weeks. ABP and the renal excretory function were studied in anesthetized rats, and expression of endothelial nitric oxide synthase (eNOS) mRNA in the isolated thoracic aorta were measured. In the 2K1C rats, GD flower extract significantly decreased ABP while increased significantly eNOS mRNA levels. GD flower extract did not exert a diuretic effect in either SO and 2K1C rats since there was no change in observed urine excretion, but it did tend to attenuated the renal tubular damage caused by renovascular hypertension. GD flower extract was anti-hypertensive in this model of renovascular hypertension and problably acts via the endothelial nitric oxide signaling pathway.